MODEL PEMBELAJARAN BBL2M (BRAIN BASED LEARNING DAN MODEL MIND MAPPING) UNTUK MENINGKATKAN HASIL BELAJAR DAN BERPIKIR KRITIS SISWA SMA NEGERI 1 AMAHAI - Lea Olivia Wattimena; H Tuaputty; S I. A Salmanu (BIOPENDIX, 2019)
Background: The process of learning biology as one part of the whole process of education in schools has an important role in efforts to improve students' biological abilities, this study aims to determine the learning outcomes and critical thinking of students by using a brain based learning learning model combined with a mind learning model mapping on the concept of biodiversity. Method: This research was conducted at Amahai 1 High School, and the data obtained were analyzed descriptively. The object of research is 21 students in class X MIA. Results: Research shows that increasing student learning outcomes and critical thinking on biodiversity material by using a brain based learning model combined with a mind mapping model gets a pretty good improvement. This is consistent with the analysis of data on the percentage obtained from the results of the initial and final tests. Increased critical thinking can be seen by using 5 aspects with indicators on the final test and cognitive aspects. Conclusion: The application of the Brain based learning model and the Mind mapping model can improve student learning outcomes and critical thinking